Entrapment mediates the relationship between depression and suicidal ideation among STD clinic attendees in shanghai, china: an analysis of the integrated motivational-volitional model - Yang Ni; Hantao Wu; Ruijie Gong; Yong Cai (BMC Psychology)
Abstract Background The aim of this study was to investigate the association between depression and suicidal ideation among attendees of a sexually transmitted diseases (STD) clinic in Shanghai, China, using an intertheoretical psychosocial framework. Methods We recruited 910 attendees from STD clinics for this cross-sectional study. We gathered data on sociodemographic factors, psychosocial variables, and suicidal ideation using a structured questionnaire that incorporated the PHQ-9, Defeat Scale, and Entrapment Scale. Logistic regression analysis was applied to examine the association between psychosocial variables and suicidal ideation. Furthermore, mediation analysis was conducted to explore the indirect effect of depression on suicidal ideation. Results The percentage of reported suicidal ideation among participants was 24.0%. Sex(OR = 0.645[0.474–0.879]), age(OR26 − 40=2.564[1.679–3.917], OR41 − 60=4.944[2.953–9.277], OR> 61=5.192[2.484–10.852]), highest educational level(ORhigh school=1.542[1.013–2.347]), current marital status(ORmarried=2.159[1.560–2.990], ORdivorced=2.148[1.063–4.340]), depression(OR = 0.810[0.781–0.840]), entrapment(OR = 0.928[0.916–0.940]), and defeat(OR = 0.927[0.913–0.941]) were significantly associated with suicidal ideation. The mediation role of entrapment was significant(indirect effect = 0.012, p < 0.001). Conclusions Our findings confirm the applicability of the Integrated Motivational-Volitional (IMV) model to the studied population. Importantly, entrapment emerged as a significant mediator in the relationship between depression and suicidal ideation among individuals attending STD clinics, highlighting its role in the pathway from depression to suicidal ideation. This underscores the need for tailored interventions addressing entrapment in this high-risk group to mitigate the risk of suicidal ideation.